Geometrical optimisation of vehicle shock dampers with magnetorheological fluid. (15th November 2010) - Parlak, Zekeriya; Engin, Tahsin; Ari, Vedat; Sahin, Ismail; , Ismail Calli
Magnetorheological (MR) dampers have attracted interest from suspension designers and researchers because of their variable damping feature, mechanical simplicity, robustness, low power consumption and fast response. Therefore, optimisation of such devices is of particular interest to achieve optimal vibration control. This study deals with the geometrical optimisation of an MR shock damper using Taguchi experimental design approach. The optimal solutions of the MR damper were evaluated using analytical equations, which give the dynamic range of the damper under consideration. Optimal geometrical values obtained provided most performance in consideration of other nine alternatives of Taguchi experimental design specified for the study.